Emergence of blaNDM– 1-Carrying Aeromonas caviae K433 Isolated From Patient With Community-Acquired Pneumonia - Luo, Xinhua; Mu, Kai; Zhao, Yujie; Zhang, Jin; Qu, Ying; Hu, Dakang; Jia, Yifan; Dai, Piaopiao; Weng, Jian; Wang, Dongguo; Yu, Lianhua (Frontiers in Microbiology, 2022)
To demonstrate the detailed genetic characteristics of a blaNDM-1-carrying multidrug-resistant Aeromonas caviae strain, the complete genome of the A. caviae strain K433 was sequenced by Illumina HiSeq and Oxford nanopore platforms, and mobile genetic elements associated with antibiotic resistance genes were analyzed by a series of bioinformatics methods. A. caviae K433 which was determined to produce class B carbapenemase, was resistant to most antibiotics tested except amikacin. The genome of K433 was consisted of a chromosome cK433 (6,482-kb length) and two plasmids: pK433-qnrS (7.212-kb length) and pK433-NDM (200.855-kb length), the last being the first investigated blaNDM-carrying plasmid from Aeromonas spp. By comparison of the backbone and MDR regions from the plasmids studied, they involved a highly homologous sequence structure. This study provides in-depth genetic insights into the plasmids integrated with blaNDM-carrying genetic elements from Aeromonas spp.